Assessment of Counseling Self-Efficacy: Validation of the German Counselor Activity Self-Efficacy Scales-Revised - Hahn, Daniela; Weck, Florian; Witthöft, Michael; Kühne, Franziska (Frontiers in Psychology, 2021)
Background: Many authors regard counseling self-efficacy (CSE) as important in therapist development and training. The purpose of this study was to examine the factor structure, reliability and validity of the German version of the Counselor Activity Self-Efficacy Scales-Revised (CASES-R). Method: The sample consisted of 670 German psychotherapy trainees, who completed an online survey. We examined the factor structure by applying exploratory and confirmatory factor analysis to the instrument as a whole. Results: A bifactor-ESEM (exploratory structural equation modeling) model with one general and five specific factors provided the best fit to the data. Omega hierarchical coefficients indicated optimal reliability for the general factor, acceptable reliability for the Action Skills-Revised (AS-R) factor and insufficient estimates for the remaining factors. The CASES-R scales yielded significant correlations with related measures, but also with therapeutic orientations. Conclusion: We found support for the reliability and validity of the German CASES-R. However, the subdomains (except AS-R) should be interpreted with caution, and we do not recommend the CASES-R for comparisons between psychotherapeutic orientations.